Faktor-Faktor Yang Mempengaruhi Preferensi Mahasiswa Terhadap Pengambilan Keputusan Menjadi Nasabah Perbankan Syariah (Studi Pada Mahasiswa S1 Ekonomi Islam Universitas Brawijaya Malang) - SE, Muthiarani Nilamsar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
In general, people need to know the insight of the banking system in Indonesia so that people can choose what banking system they will use to manage and save the funds obtained. The problem in this research is how internal factors of customers can influence them in activities to decide on their choice to use a certain banking system or banking type. External influences given to customers will certainly differs to how much perception and knowledge of the customers about the banking system and other internal influences such as economy, family, and religiosity that will affect the customers as they enter the decision-making stage. Based on the results of research obtained using logistic regression analysis it is found that the perception factor, knowledge, family, and religiosity can have a positive and significant impact on customer decisions in choosing banking types. While the economic factor does not significantly influence the decision of the customers in choosing the banking system.Keywords: Sharia banking, student preference, logistic regression